Thermodynamic study of zinc antimonides by the electromotive force measurements - Aytekin R. Aghayeva; Sakina H. Mammadova; Dunya M. Babanly; Yasin I. Jafarov; Dilgam B. Tagiyev (Конденсированные среды и межфазные границы)
Zinc antimonides and phases based on them are of great interest as earth-abundant, low-cost, and environmentally friendly thermoelectric materials. The present work demonstrates the results of a thermodynamic study of the ZnSb and Zn4Sb3 compounds by a low-temperature electromotive force (emf) method with a glycerol electrolyte in the 300-430 K temperaturesrange.